ANALISIS PENGARUH NILAI FUNGSIONAL, EMOSIONAL DAN SOSIAL TERHADAP LOYALITAS (STUDI PADA PENGGUNA NON-KOMUNITAS DAN ANGGOTA KOMUNITAS SEPEDA MOTOR MEREK YAMAHA VIXION DI KOTA PONTIANAK) - B11108053, Modestus Riko (Jurnal Manajemen Update, 2013)
The purpose of this study is to investigate and analyze the influence of the functional value, emotional value and social value of loyalty to the user community and non-community members Vixion Yamaha brand motorcycles in Pontianak. The population in this study were all non-community users Yamaha Vixion in Pontianak and all members of the Yamaha Vixion Club Indonesia Chapter Pontianak. The number of samples taken in this study of 50 non-community samples and 50 samples of community members Yamaha Vixion Club Indonesia Chapter Pontianak. This study and the survey method using pieces using SPSS 16.0 in testing the validity, reliability, normality, multicollinearity, and heteroskedasitas, multiple linear regression, as well as simultaneous testing and Persia in determining the outcome of research. F test of non-community users, the value of F count is much greater than F table (401 937 with a significance level of 0.000, where the figure is less than 0.05) and F test users, community members, the value of F count is much greater than F table (132.001 with a significance level of 0.000, where the figure is less than 0.05), which means that the independent variable has a positive and significant effect on the dependent variable. Based Persia test (t test) has been done can be concluded that for non-community respondents of the three variables that have an impact on loyalty is partially functional value variable (X1) and social value (X3). While the variables that affect not partially emotional value is variable (X2). As for the respondent members of the community three independent variables in Persia all have an impact on customer loyalty. Keywords: Functional Value, Emotional Value, Social Value and Loyalty